Role of PEGylated CdSe-ZnS quantum dots on structural and functional properties of electrospun polycaprolactone scaffolds for blood vessel tissue engineering. (15th May 2021) - Columbus, Soumya; Painuly, Diksha; Nair, Renjith P.; Krishnan, V. Kalliyana
Graphical abstract: Highlights: Electrospun PCL/CdSe-ZnS scaffolds were fabricated for blood vessel applications. PCL/Q-dot composite exhibited narrower pore size than pristine PCL scaffolds. Scaffolds demonstrated superior mechanical properties than native blood vessels. Incorporation of Q-dots into the scaffolds does not elicit any cytotoxic effects. PCL/Q-dot composite supported better coverage of endothelial cells. Abstract: Conjugation of quantum dots (Q-dots) into tissue engineering scaffolds is extremely beneficial for designing composite scaffolds imparting multifunctional properties. In the present work, we report the efficacy of incorporating the PEGylated CdSe-ZnS (Q-dots) into electrospun poly(caprolactone)(PCL) scaffolds whose properties were evaluated for small diameter blood vessel applications. Incorporation of Q-dots was found to result in significant reduction in fiber diameter of electrospun scaffolds. Corresponding pore size ranges varied from 12 to 36 µm for composite scaffold compared with 12–60 µm in bare scaffold. Both PCL and composite scaffolds were found to possess better mechanical strength and elasticity than that of native arteries. Contact angle measurements revealed hydrophobic nature of scaffolds which significantly improved upon modification with fibrin. PCL/Q-dot composite scaffolds were found to possess optimum micro-structure for supporting uniform endothelial cell growth after 5 days of culture compared to the pristine PCL scaffold.